Patient Safety as a Core Focus in Multidisciplinary Healthcare Teams: Systamatic Review - Almutari, Dhafi Aish Dhafi; Alghamdi, Ahmed Saeed Ahmed; Majhali, Samirah Yahya Mohammed; Alshamrani, Abdulaziz Abdullah Ali; Alshehri, Faris Mohammed Sultan; Algamdi, Mohammd Saeed Abdullah; Alshamrani, Waleed Ali Muflih (Journal of Neonatal Surgery, 2025)
Background: As the prevalence of ailments and diseases worldwide increases, medical facilities and services are also evolving. However, the resources are limited, so by the time the best solutions are implemented, a new virus or bacteria emerges. Now is the time when patient care requires a multidisciplinary approach; hence, MDTs, or multidisciplinary teams, are set up to meet the requirements of patient care. This present study will evaluate the scenario in Saudi Arabia. This is a review study based on the previous research conducted by the authors in Saudi Arabia and other developing countries. The development of MDTs in recent years, the present scenario, and future prospects will be evaluated. Some of the major challenges and barriers will also be discussed. Study Objectives: The objective of this study is to identify global patient safety frameworks in the context of Saudi Arabia, with a focus on the multidisciplinary approach to safety culture and interprofessional collaboration. Materials and Methods: The Study is based on the previous studies conducted from 2015 to 2024. A total of 38 studies were considered by the authors of Saudi Arabia and other international authors. Studies were collected after deciding on the inclusion and exclusion criteria.